Integration of Arabic Language Learning through the All in One System Approach at Ar-Raudhatul Hasanah Islamic Boarding School, Lumut - Siregar, Irsal Amin; Pulungan, Muhammad Yusuf; Ritonga, Sylvia Kurnia (Universitas Muhammadiyah Sumatera Barat, 2025)
Arabic language learning in modern Islamic boarding schools focuses on memorization and repetition, while the communicative and linguistic dimensions have not been optimally integrated. Therefore, it is necessary to design a development model that combines academic learning activities in the classroom with communicative and contextual language practices. This study aims to describe and analyze the method of developing Arabic language learning activities through the All in One System approach at Ar-Raudhatul Hasanah Islamic Boarding School. This study uses a qualitative descriptive approach, using data collection techniques such as observation, interviews, and document analysis. Data analysis was carried out through the interactive model of Miles, Huberman, and Saldaña, including data reduction, display, and conclusion drawing. Data validity was ensured through source triangulation, technical triangulation, and member checking. The findings of this study revealed three models of Arabic language learning development: Mufradāt learning developed using the ADDIE model, emphasizing systematic planning and continuous evaluation; grammar learning developed through the ASSURE model, which focuses on learner characteristics and active participation; and and language skills learning (istimā‘, muḥādathah, qirā’ah, and kitābah) are developed through the CTL (Contextual Teaching and Learning) model, which emphasizes experience-based learning. This study concludes that the All in One System has created a dynamic and participatory Arabic language learning ecosystem, positioning language as a living practice shaped by social and cultural interactions.